Identification of Malay culture in Rarra characters in Nussa Rarra animation - Viona Karmenita; Fachri Helmanto (LADU: Journal of Languages and Education, 2022)
Background: Nussa Rarra animation is a children's animation in which there are many lessons that can be taken for everyday life. Both in terms of behavior, humility, and leads to religion. In this animation, of course, there is a culture attached to the animated characters in it. Purpose: This research was conducted with the aim of identifying the Malay culture contained in the character of Rarra in the animation of Nussa Rarra Design and methods: This research was conducted using a qualitative approach. The type of research used is content analysis method. Results: The results of this study indicate that in Rarra's character there is polite behavior, soft spoken, honest, and someone who is so very friendly, this is assumed to be a form of Malay culture. And it can be concluded that there are several forms of Malay culture that are applied to the character of Rarra in the Nussa Rarra animation, namely politeness, gentle speech, honesty, and a friendly attitude.